How are vineyards management strategies and climate-related conditions affecting economic performance? A case study of Chilean wine grape growers - Carlos Bopp; Roberto Jara-Rojas; Alejandra Engler; Miguel Araya-Alman (Wine Economics and Policy, 2022)
In wine grape production, growers decide between alternative management strategies of the vineyard that have direct consequences on competitiveness. The aim of this study is to evaluate the impact on economic performance of four management strategies: training system, reserve quality production, irrigation method, and mechanization of labors. The data used in the study comes from face-to-face interviews to 336 wine grape growers of Central Chile, which was complemented with climatic variables retrieved from Geographic Information Systems. A log-log regression model of total value product (TVP) for the main variety grown in the vineyard was estimated, using production factors, vineyards' attributes, management strategies and climate-related conditions as explanatory variables. An interesting contribution of this study is the identification of TVP functions for land, fertilizers, fungicides, other agrochemicals, labor, and age of vines. Our results show that the training system has the most impact on TVP, where tendone-trained vineyards demonstrated 63% higher TVP than those vertically trained when holding all other variables constant. Reserve quality production also has a positive effect on TVP, increasing it by 25% compared to vineyards producing varietal quality grapes. In contrast, the use of pressurized irrigation systems and mechanization in harvesting do not present a significant effect on TVP. The findings of this paper represent an advance in the understanding of the economic performance factors associated with wine grape growing and could serve to guide on-farm decisions and sectoral policies in pursuing the competitive development of wine grape growers.
Keywords: 330; production function; vineyard management; wine grape growing; economic performance